A Multi-Catalytic Sensing for Hydrogen Peroxide, Glucose, and Organophosphorus Pesticides Based on Carbon Dots - Li, Ping; Sun, Xiang-Ying; Shen, Jiang-Shan (Frontiers in Chemistry, 2021)
In this work, a facile one-pot hydrothermal route was employed to synthesize a series of fluorescent carbon dots (CDs) by using 20 natural amino acids, respectively, as the starting materials. It was found that the CDs synthesized by phenylalanine could possess the intrinsic peroxidase-like activity that could effectively catalyze traditional peroxidase substrate like 3, 3′, 5, 5′-tetramethylbenzidine (TMB) in the presence of H2O2, to produce a blue solution, thereby a catalytic sensing system for H2O2 has been developed. On the basis of this catalytic reaction, and taken together that glucose oxidase (GOx) can catalyze the hydrolysis of glucose to generate H2O2, a sensitive catalytic sensing system for glucose could be further established. Furthermore, this catalytic reaction, taken together with two enzymatic catalytic systems of acetylcholinesterase (AChE) and choline oxidase (CHO), a highly sensitive multi-catalytic sensing system could be successfully developed for organophosphorus (OPs) pesticides such as dimethoate, DDVP and parathion-methyl. Limit of detections (LODs) of H2O2 and glucose were estimated to be 6.5 μM and 0.84 μM, respectively. LOD of sub nM level could be achieved for tested dimethoate, DDVP and parathion-methyl OPs pesticides. The established sensing systems can exhibit good practical application performance in serum and several fruit samples.